Evaluasi Kapasitas Saluran Drainase Eksisting terhadap Debit Banjir Rencana di Kecamatan Gunung Anyar, Surabaya - Infaqi, Ta’faqur Wahyu Nur; Saves, Faradlillah (Jurnal Sains dan Teknologi (JSIT), 2025)
The Gunung Anyar area of Surabaya has experienced rapid population growth and development, leading to a decline in green open spaces and water infiltration areas. This condition increases the risk of inundation and flooding due to the limited capacity of the existing drainage system. This study aims to evaluate the capacity of the existing drainage channels against the design flood discharge based on hydrological and hydraulic analyses. The hydrological analysis shows that the highest design flood discharge occurs in Sub-watershed 5 at 0.404 m³/s, while the lowest is found in Sub-watershed 6 at 0.096 m³/s. Meanwhile, the hydraulic analysis indicates that the highest channel capacity is in Channel 10 at 0.858 m³/s, and the lowest in Channel 6 at 0.097 m³/s. A comparison between hydrological and hydraulic discharges shows that several channels have smaller capacities than the design flood discharge (Q_hydraulic < Q_hydrologic), which may lead to inundation, particularly in Channels 1, 2, 5, 6, and 7. On the other hand, Channels 3, 4, 8, 9, and 10 are still capable of accommodating runoff effectively. The results of this evaluation can serve as a basis for planning drainage capacity improvements in the Gunung Anyar area to reduce future flood risks